Digital platform ClimMob streamlines participatory research in agriculture: The latest release of the open-source platform enables intuitive use and robust analysis - 1000FARMS Platform; De Sousa, Kaue (2025)
This poster presents how ClimMob, an open-source digital platform developed in collaboration with members from the Alliance of Bioversity International and CIAT, is supporting the large-scale implementation of tricot, a participatory on-farm testing method. By improving user-friendliness, integrating multilingual support, standardizing protocols, and capturing detailed metadata, ClimMob enables inclusive, high-quality, and scalable data collection in diverse contexts. The platform supports researchers, breeding programs, and genebanks in designing robust trials and analyzing performance data and farmer preferences. Integrated within the 1000FARMS platform, ClimMob is empowering thousands of users to accelerate the development of climate-adapted, farmer-preferred crop varieties across 19 countries.